2021
DOI: 10.30998/formatif.v11i1.7951
|View full text |Cite
|
Sign up to set email alerts
|

Development of STEM-Based Physics Teaching Materials Integrated 21st Century Skills (4C) and Characters

Abstract: Teaching materials currently available are mostly centered on textbook and tasks. Moreover, it is rarely implanted with 21st century skills and character values so that students find it difficult when solving problems related to life. STEM-based teaching materials developed are presented with characteristics of fluid information which is complemented by discussions, practicum, and project activities related to STEM aspects and integrated with 21st century skills (4C) and character values so that students are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Then the research conducted by Syahiddah with the results of the validity of the development of STEM-based physics e-modules on sound material in Senior High School was valid and feasible to use with a score of 3.54 and a percentage of 89% with very high criteria [12]. Finally, the research conducted by Wayudo with the results of the feasibility test for developing integrated learning material STEM 21st-century skills, and student character was very feasible to use with a presentation of 91.36% [13].…”
Section: Introductionmentioning
confidence: 82%
“…Then the research conducted by Syahiddah with the results of the validity of the development of STEM-based physics e-modules on sound material in Senior High School was valid and feasible to use with a score of 3.54 and a percentage of 89% with very high criteria [12]. Finally, the research conducted by Wayudo with the results of the feasibility test for developing integrated learning material STEM 21st-century skills, and student character was very feasible to use with a presentation of 91.36% [13].…”
Section: Introductionmentioning
confidence: 82%
“…In the last learning, students were asked to make project assignments in the form of simple tools related to materials. This activity was carried out to hone students' skills in communicating and collaborating in solving problems, making decisions, and providing opportunities for students to work in the period that has been observed in producing products (Fitriani 2020;Waluyo & Wahyuni 2021). Students' communication and collaboration skills are expected to increase after the learning process using STEM-based e-learning.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of the findings of this study with previous studies shows suitability and alignment. Previous studies using multiculturalism approaches, local wisdom, communicative approaches, and scientific approaches have also shown that the development of textbooks oriented towards social integration and 21st century skills have a positive impact on improving students' abilities (Kholis & Azmi, 2023;Susanto et al, 2022;Waluyo & Wahyuni, 2021;Ibrahim, Abduh, & Korompot, 2023). The findings of this study are in line with the concept of 21st century education which emphasizes critical thinking skills, creativity, communication, and collaboration (Azhary & Ratmanida, 2021;Farida, Supardi, & Muchtar, 2023;Thornhill-Miller et al, 2023;Tohani & Aulia, 2022).…”
Section: Discussionmentioning
confidence: 98%